Aptamer-Based Biosensors for Environmental Monitoring - McConnell, Erin M.; Nguyen, Julie; Li, Yingfu (Frontiers in Chemistry, 2020)
Due to their relative synthetic and chemical simplicity compared to antibodies, aptamers afford enhanced stability and functionality for the detection of environmental contaminants and for use in environmental monitoring. Furthermore, nucleic acid aptamers can be selected for toxic targets which may prove difficult for antibody development. Of particular relevance, aptamers have been selected and used to develop biosensors for environmental contaminants such as heavy metals, small-molecule agricultural toxins, and water-borne bacterial pathogens. This review will focus on recent aptamer-based developments for the detection of diverse environmental contaminants. Within this domain, aptamers have been combined with other technologies to develop biosensors with various signal outputs. The goal of much of this work is to develop cost-effective, user-friendly detection methods that can complement or replace traditional environmental monitoring strategies. This review will highlight recent examples in this area. Additionally, with innovative developments such as wearable devices, sentinel materials, and lab-on-a-chip designs, there exists significant potential for the development of multifunctional aptamer-based biosensors for environmental monitoring. Examples of these technologies will also be highlighted. Finally, a critical perspective on the field, and thoughts on future research directions will be offered.